KARAKTERISASI HIDROLISAT PROTEIN KEDELAI HASIL HIDROLISIS MENGGUNAKAN PROTEASE DARI TANAMAN BIDURI (Calotropis gigantea) - Yuli Witono; Aulanni’am Aulanni’am; Achmad Subagio; Simon Bambang Widjanarko (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 2007)
Properties of soy protein hydrolysate produced by protease from biduri plant were studied. The soy protein hydrolysate had different properties due to various concentrations and hydrolysis times of protease from biduri. Enzymatic hydrolysis of the soy protein decreased significantly in the TBA value. This process increased the soluble protein content and promoted the Maillard reaction, resulting in a more brown color. Moreover, the soy protein hydrolysate had a higher value of ‘umami’ taste by organoleptic evaluation.